2006
DOI: 10.1007/s11771-006-0026-4
|View full text |Cite
|
Sign up to set email alerts
|

Settlement calculation for long-short composite piled raft foundation

Abstract: The mechanism of long-short composite piled raft foundation was discussed. Assuming the relationship between shear stress and shear strain of the surrounding soil was elasto-plastic, shear displacement method was employed to establish the different explicit relational equations between the load and the displacement at the top of pile in either elastic or elasto-plastic period. Then Mylonakis & Gazetas model was introduced to simulate the interaction between two piles or between piles and soil. Considering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Although the stress correction method is relatively simple, it is difficult to determine the pile-soil stress ratio and the stress correction coefficient of the composite foundation, and the role of long and short piles is ignored during the calculation process. According to the shear displacement method, Zhao et al [12,13] introduced a pile-pile and pile-soil interaction model based on specific assumptions. With the effect of the bedding layer considered, a method to calculate the settlement of a composite foundation was proposed based on the bedding-pile-soil joint action, but it did not take into account relevant problems caused by loess collapsibility.…”
Section: Calculation Of Settlement Of Composite Pile Foundation With Long and Short Piles In Loess Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the stress correction method is relatively simple, it is difficult to determine the pile-soil stress ratio and the stress correction coefficient of the composite foundation, and the role of long and short piles is ignored during the calculation process. According to the shear displacement method, Zhao et al [12,13] introduced a pile-pile and pile-soil interaction model based on specific assumptions. With the effect of the bedding layer considered, a method to calculate the settlement of a composite foundation was proposed based on the bedding-pile-soil joint action, but it did not take into account relevant problems caused by loess collapsibility.…”
Section: Calculation Of Settlement Of Composite Pile Foundation With Long and Short Piles In Loess Areasmentioning
confidence: 99%
“…In terms of calculating the settlement deformation of long and short piles, Yang et al [11] proposed a practical settlement calculation method for composite pile foundations with long and short piles and applied it to the analysis of the settlement of a high-rise residential building. Zhao et al [12,13] established a calculation model for the settlement of composite pile foundations with long and short piles based on the shear displacement method with certain simplifying assumptions. Hong Y et al [14] carried out a field study on the downdrag and dragload of two pairs of bored piles installed in consolidating ground.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that reinforcing the shallow soft soil with stone columns can effectively improve the bearing interaction of the raft. Zhao et al [21] discussed the mechanism of the long-short composite pile-raft foundation. Considering the influence of the cushion, the flexibility factors of the interaction were determined and a settlement calculation method for the long-short composite pile-raft foundation was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al [7] proposed a simplified analytical model for the optimal selection of cushion stiffness. Zhao et al [26] developed a settlement calculation method for a long-short pile composite pile-raft foundation. Zhang and Shi [27] constructed a mechanical model of a pile-piercing cushion and a method to calculate pile-soil interaction.…”
Section: Introductionmentioning
confidence: 99%